Exploring the Influence of Artificial Intelligence and Religiosity on Green Purchase Intention: An Empirical Study From Banglades - Nabila Islam; Hanim Hj Misbah (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by ERA